Transgenic expression of the rice Xa21 patternrecognition receptor in banana (Musa sp.) confers resistance to Xanthomonas campestris pv. musacearum - Tripathi, J.N.; Lorenzen, J.H.; Bahar, O.; Ronald, Pamela C.; Tripathi, L. (Wiley, 2014)
Banana Xanthomonas wilt (BXW), caused by the bacterium Xanthomonas campestris pv.musacearum (Xcm), is the most devastating disease of banana in east and central Africa. Thespread of BXW threatens the livelihood of millions of African farmers who depend on bananafor food security and income. There are no commercial chemicals, biocontrol agents orresistant cultivars available to control BXW. Here, we take advantage of the robust resistanceconferred by the rice pattern-recognition receptor (PRR), XA21, to the rice pathogenXanthomonas oryzae pv. oryzae (Xoo). We identified a set of genes required for activation ofXa21-mediated immunity (rax) that were conserved in both Xoo and Xcm. Based on theconservation, we hypothesized that intergeneric transfer of Xa21 would confer resistance toXcm. We evaluated 25 transgenic lines of the banana cultivar ‘Gonja manjaya’ (AAB) using arapid bioassay and 12 transgenic lines in the glasshouse for resistance against Xcm. About50% of the transgenic lines showed complete resistance to Xcm in both assays. In contrast, allof the nontransgenic control plants showed severe symptoms that progressed to completewilting. These results indicate that the constitutive expression of the rice Xa21 gene inbanana results in enhanced resistance against Xcm. Furthermore, this work demonstrates thefeasibility of PRR gene transfer between monocotyledonous species and provides a valuablenew tool for controlling the BXW pandemic of banana, a staple food for 100 million people ineast Africa.